Exploring the centrality of nonviolent communication for resolution of conflicts for a culture of peace - Kundu, Vedabhyas (CIC. Cuadernos de Información y Comunicación, 2023)
At a time when humanity finds itself enveloped by conflicts of different kinds, violence, greed and crimes at various levels, the world hungers for peace and nonviolence. The United Nations talks about how conflict and violence ‘are currently on the rise’. It talks of the rising involvement of non-state actors like political militias, criminal and international terrorist groups. Amongst the dominant forces behind conflicts according to the United Nations are unresolved regional tensions, breakdown in the rule of law, absent or co-opted state institutions, illicit economic gain and the scarcity of resources. (https://www.un.org/en/un75/new-era-conflict-and-violence) The aim is to constantly work to find frameworks and practical models to end these conflicts. The challenge is not just to find solutions for cessation of these conflicts but also to address the root cause of these violence. In most of these conflicts, there are attempts to encourage sanitization of language and distort reality; in many occasions there is use of language to demonize groups and normalize violence. Communication hence can be said to fuel all forms of violence – direct, structural and cultural. Using case studies of integrating Mahatma Gandhi’s nonviolent communication in different settings and social institutions, the paper will look at how this approach of nonviolent communication can help in bringing change in attitude and behavior of the conflicting parties and aid in the resolution of the conflict.